Pengaruh Sikap Skeptisme, Profesionalisme Dan Locus Of Control Pada Kualitas Audit Investigatif Dalam Mengungkap Fraud - Indraswari, I Gusti Agung Ayu Pramita; Dewi, Putu Pande R. Aprilyani; Pradnyani, I Gusti Agung Arista; Sumantri, I.G.A.N. Alit (Politeknik Negeri Ambon, 2024)
This study aims to determine the influence of skepticism, professionalism, and locus of control on audit quality in the context of uncovering fraud. The hypothesis in this study is that skepticism has a positive and significant effect on audit quality in uncovering fraud, professionalism has a positive and significant effect on audit quality in uncovering fraud but locus of control has a negative and insignificant effect on audit quality in uncovering fraud. The research method used is multiple linear regression statistical methods. Quantitative data is primary data. Primary data in the form of questionnaires were collected from auditors at KAP Denpasar City. The results showed that auditor skepticism and auditor professionalism had a positive effect on audit quality in uncovering fraud. However, locus of control hurts audit quality in disclosing fraud. Keywords: Skepticism, professionalism, locus of control, investigative audit quality, fraud